2021
DOI: 10.1021/acsami.1c02169
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the Durability of Intermetallic Mo–Ni Compounds in the Hydrogen Evolution Reaction

Abstract: Molybdenum–nickel materials are catalysts of industrial interest for the hydrogen evolution reaction (HER). Well-characterized surfaces of the single-phase intermetallic compounds Ni7Mo7, Ni3Mo, and Ni4Mo were subjected to accelerated durability tests (ADTs) and thorough characterization to unravel whether crystallographic ordering affects the activity. Their intrinsic instability leads to molybdenum leaching, resulting in higher specific surface areas and nickel-enriched surfaces. These are more prone to form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Computational studies by Bader charge analysis, 58–62 give us the reasoning of the experimentally observed inverse charge transfer in the Ni 73 Mo alloy. 63 A 4 × 4 Ni (111) surface was constructed with 6 layers consisting of 80 atoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational studies by Bader charge analysis, 58–62 give us the reasoning of the experimentally observed inverse charge transfer in the Ni 73 Mo alloy. 63 A 4 × 4 Ni (111) surface was constructed with 6 layers consisting of 80 atoms.…”
Section: Resultsmentioning
confidence: 99%
“…55,56 The E  of NMH-24 is closer to 1.53 V versus the reversible hydrogen electrode (RHE), which is suitable for creating a hole accumulation layer at the anode-electrolyte interface for triggering the water oxidation process. Computational studies by Bader charge analysis, [58][59][60][61][62] give us the reasoning of the experimentally observed inverse charge transfer in the Ni 73 Mo alloy. 63 A 4 × 4 Ni (111) surface was constructed with 6 layers consisting of 80 atoms.…”
Section: Inverse Charge Transfermentioning
confidence: 87%
“…The developed protocol allows for the synthesis of stable (Sn,Pb,Bi)Pt bulk materials, on which not only a broad range of analytical investigations are possible but also the return to a well investigated initial state is possible by polishing of the surface. This has proven especially useful in the field of electrocatalysis as all investigations can be conducted on an identical sample. ,,, , The use of unsupported bulk materials reduces complexity and allows for the determination of intrinsic materials properties, resulting in a great benefit to understand material changes also in heterogeneous gas-phase catalysis, such as steam reforming , or hydrogenation reactions by using powdered materials.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, the investigation of bulk samples has proven to be beneficial as simple polishing can revert any changes to the thermodynamically equilibrated material. This allows for investigations with identical starting points by multiple techniques in different reactions. ,, …”
Section: Introductionmentioning
confidence: 99%
“…As reported previously, the dissolution of Mo has been shown to occur from surface Ni-Mo alloys under HER relevant conditions. 22,41 An activity decrease at a positive potential due to the dissolution of Mo oxides is a cause of performance loss. This will present stability issues, especially during the intermittent operation of industrial electrolyzers (the cathode potential changes in the anodic direction immediately aer the electrolyzer is disconnected from the power source).…”
Section: Electrochemical Stability Characterizationmentioning
confidence: 99%